Identification of Putative Natriuretic Hormones Isolated from Human Urine - Kramer, Herbert J. (Frontiers in Endocrinology, 2015)
This brief review describes some representative methodological approaches to the isolation of putative endogenous inhibitors of epithelial sodium transport - i. e. as ouabain-like factors (OLF) that inhibit the sodium transport enzyme Na-K-ATPase or inhibit the epithelial sodium channel (ENaC). Gel chromatography and reverse-phase (RP)-HPLC of lyophilized and reconstituted 24h-urine from salt-loaded healthy humans led to two active fractions, a hydrophilic OLF-1 and a lipophilic OLF-2 whose mass (Ms)-spectroscopic data indicate a Mr of 391 (1,2). Further identification was attempted by Ms-, IR-, UV- and 1H-NMR- spectroscopy. OLF-1 and OLF-2 may be closely related if not identical to (di)ascorbic acid or its salts such as vanadium (V)-Vv-diascorbate with Mr 403 (3) and VIV-diascorbate. OLF-1 and Vv-diascorbate are about 10-fold stronger inhibitors of Na-K-ATPase than OLF-2 and VIV-diascorbate, respectively. In conscious rats, i.v. infusion of OLF-1 and OLF-2 resulted in a strong natriuresis. In a similar study Cain et al. (4) isolated a sodium transport inhibitor from the urine of uremic patients by gel chromatography and RP-HPLC. In uremic rats a natriuretic response to the injection of the active material was found. Xanthurenic acid 8-O-ß-D-glucoside (Mr 368) and xanthurenic acid 8-O-sulfate (Mr 284) were identified as endogenous inhibitors of sodium transport acting, e.g. by ENaC blockade. No definite relation to blood pressure, body fluid volume or sodium balance has been reported for any of these above factors and further studies to identify the natriuretic and/or ouabain-like compound(s) or hormone(s) will be needed.